The Concept of Production, Distribution, and Consumption in Islamic Economics - Rizky Maidan Ilmy; Iwan Setiawan (Review of Islamic Economics and Finance (RIEF), 2019)
During the last two decades, two economic ideologies that experienced world development, namely socialism and capitalism, competed to prove themselves as the most rightful and the most potential in solving people's economic problems. Yet, both of them were judged failed to serve solutions in solving people's main classic economic problem. Islamic Economy was introduced as the alternative in solving the problems. One of the ideas from Islamic Economy ideologies is the concept of production, distribution, and consumption. The research methodology used was the descriptive-qualitative method; the data collection was conducted by combining theories from different references. The research aims to acknowledge how production, distribution, and consumption in the Islamic Economy works. The research findings include: 1) the production concept in Islamic Economy should be based on three main basic aspects, namely the aspect of belief, knowledge, and deed; 2) the production concept in Islamic Economy should be based on the basic principle of Islamic Economy namely individual freedom, social insurance, prohibition in accumulating wealth, and fair wealth distribution; 3) the concept of consumption in Islamic Economy to only fulfill daily needs, not the wants.